2022
DOI: 10.1186/s12905-022-02007-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of self-care education based on the health literacy index on self-care and quality of life among menopausal women: a randomized clinical trial

Abstract: Purpose Aging is associated with many different health-related challenges for women such as menopause and its associated problems. Self-care (SC) is a factor with potential effects on menopause and its consequences. SC education based on health literacy has the potential to improve menopausal women’s SC. The aim of this study was to evaluate the effects of SC education based on the health literacy index (HLI) on SC and quality of life (QOL) among menopausal women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…Another study was conducted to assess the impact of self-care education on menopausal women's quality of life and self-care using the health literacy index. The results showed that the quality of life and self-care of menopausal women can be significantly enhanced by health-literacy-index-based self-care education, which can also be utilized to improve menopausal women's health-related outcomes [42]. In the present study, a positive correlation was identified between the various domains of self-care and the different categories of menopausal symptoms.…”
Section: Discussionsupporting
confidence: 54%
“…Another study was conducted to assess the impact of self-care education on menopausal women's quality of life and self-care using the health literacy index. The results showed that the quality of life and self-care of menopausal women can be significantly enhanced by health-literacy-index-based self-care education, which can also be utilized to improve menopausal women's health-related outcomes [42]. In the present study, a positive correlation was identified between the various domains of self-care and the different categories of menopausal symptoms.…”
Section: Discussionsupporting
confidence: 54%
“…La menopausia está definida por la Organización de la Salud (OMS), como el cese permanente del periodo menstrual retrospectivamente por 12 meses de amenorrea consecutiva de manera natural sin causa patológica (Hossein et al, 2022), en mujeres de edades entre 45 y 55 años esto depende también de la ubicación geográfica ya que en Europa aparece a los 54 años, en América y Asia se da alrededor de los 51 años mientras que en países como México la edad promedio de este periodo se sitúa en los 48 años (Torres Jiménez & Torres Rincón, 2018).…”
Section: Introductionunclassified
“…According to this theory, humans can take care of themselves, and when this ability is compromised, the caregiver can enable them to recover their self-care ability by providing direct and compensatory care or educational-supportive care [ 22 ]. Therefore, the necessity of improving self-care ability through education is undeniable [ 23 ].…”
Section: Introductionmentioning
confidence: 99%